The Influence of the Korean Wave on Students' Sense of Responsibility and Commitment to Local Wisdom - Ade Suherman; Wulan Sondarika; Latansa Sabati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
The purpose of this study is to analyze the influence of the Korean wave on students' attitudes of responsibility and commitment to local wisdom. This study used a quantitative approach with a survey method. The results show that the Korean wave has a significant influence on students' attitudes of responsibility, with a correlation coefficient of 0.909. The coefficient of determination value of 0.827 indicates that 82.7 percent of the variation in students' attitudes of responsibility is influenced by exposure to the Korean wave. In comparison, 17.3 percent is influenced by other factors. The Korean wave also influences students' commitment to preserving local wisdom, with a correlation coefficient value of 0.909. The coefficient of determination value of 0.826 shows that 82.6 percent of the variation in student commitment to preserving local wisdom is influenced by exposure to the Korean wave, while 17.4 percent is influenced by other factors. The influence of the Korean wave on students' attitudes of responsibility and commitment to local wisdom is constructive if supported by adequate education and supervision patterns.